Investigando o uso de aulas on-line de programação de jogos digitais no ensino básico - Silva, Thiago Reis da (2017)
The introduction of activities or even disciplines related to the teaching programming in schools has been increasingly discussed with enthusiasm in associations and commissions that deal with teaching of Computing. In Brazil, the Brazilian Computer Society (SBC) recommends that programming notions should be taught since elementary school. They argue that the associated skills, when assimilated early, contribute to the development of logical reasoning and problem solving, which contributes to increasing number of professionals in the area and also develops the vocational aptitude of teenagers. The digital games are elements that have been often used to introduce teaching programming in the schools by offering playful and interactive moments in the learning process, being attractive to the student and increasing the student's disposal to learn. Thus, this doctoral work consisted in the realization of a set of experimental studies that investigates different formats of online classes of digital games programming for elementary school students, resulting in a model of Virtual Tutoring. In this context, this work proposes: (i) to create a teaching methodology of online digital game programming that can be used on a large scale; (ii) teach game programming in schools using video lectures; and (iii) conduct empirical studies that seeks for evidences of benefits and limitations of the proposed methodology. The results obtained from such studies bring evidences that the formats are feasible and indicate a good level of understanding by the students. In addition, our results suggest that using the Virtual Tutoring format is promising for the development of digital game programming skills when programmers have few or none experience programming practice. Finally, the students' perception using Virtual Tutoring format was positive when compared with the others investigated formats.